Building Self-Confidence Foundation: The Role of Parental Attachment and Self-Concept in Children Who Memorize the Qur'an - Aqima Sholehati; Yarmis Syukur; Dina Sukma; Nurfarhanah Nurfarhanah (Universitas Ahmad Dahlan, 2023)
The research aims to analyze the following aspects: (1) parental attachment, (2) self-concept, (3) self-confidence, and (4) the relationship between parental attachment and self-concept with the self-confidence of children who memorize the Qur'an. The research utilizes a quantitative approach with a descriptive correlational design. The study population consists of 121 individuals, and a sample of 94 participants was selected using the Slovin formula and proportional random sampling technique. The research instrument employed a Likert Scale questionnaire, and data were analyzed using descriptive correlational and multiple regression analysis. The research findings reveal that (1) children who memorize the Qur'an exhibit a significantly high level of parental attachment, (2) their self-concept falls within the moderate category, (3) their self-confidence is also at a moderate level, and (4) there is a significant relationship between parental attachment and self-concept with the self-confidence of children who memorize the Qur'an. Therefore, it can be concluded that there exists a positive and significant association between parental attachment and self-concept with the self-confidence of children who memorize the Qur'an.